2006
DOI: 10.1007/s10529-006-9183-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of Penicillium minioluteum dextranase in Saccharomyces cerevisiae and its exploitation as a reporter in the detection of mycotoxins

Abstract: A dextranase gene from Penicillium minioluteum (strain IMI068219) has been cloned, sequenced and expressed in Saccharomyces cerevisiae via fusion of the DNA segment encoding the mature dextranase protein with alpha-factor signal sequence, and insertion into the GAL1-controlled expression vector pYES2/CT. Galactose-induced expression yielded extracellular dextranase activity of 0.63 units/ml and cell-associated dextranase activity of 0.48 units/ml, after 24 h incubation. The dextranase construct was introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Compared to other dextranases obtained from GenBank by BLASTX and BLASTP searches, SMCU-DEX revealed 97% amino acid sequence identity to the dextranase from P. funiculosum (accession number AJ272066) and 99.5%, 90%, and 87% identity to the enzymes from three isolates of P. minioluteum (accession numbers L41562, AF020619, and DQ394070; see Garcia et al 28 , Li et al 19 ). The deduced amino acid sequence was compared to the GenBank conserved domain and amino acid databases, which revealed that SMCU-DEX belongs to the GH49 family.…”
Section: Cloning Of the Genomic Dextranase Genementioning
confidence: 85%
See 2 more Smart Citations
“…Compared to other dextranases obtained from GenBank by BLASTX and BLASTP searches, SMCU-DEX revealed 97% amino acid sequence identity to the dextranase from P. funiculosum (accession number AJ272066) and 99.5%, 90%, and 87% identity to the enzymes from three isolates of P. minioluteum (accession numbers L41562, AF020619, and DQ394070; see Garcia et al 28 , Li et al 19 ). The deduced amino acid sequence was compared to the GenBank conserved domain and amino acid databases, which revealed that SMCU-DEX belongs to the GH49 family.…”
Section: Cloning Of the Genomic Dextranase Genementioning
confidence: 85%
“…However, only eight dextranase genes from five species of filamentous fungi plus one species of yeast have been reported to date, namely the dextranase genes from P. funiculosum (AJ272066), Penicillium marneffei ATCC 18224 (XM 002152550), P. minioluteum (L41562, DQ394070 and AF020619), Verticillium alboatrum VaMs.102 (XM 003005140), V. dahliae VdLs.17 (DS572701), and the yeast L. starkeyi (AY520537). These fungal dextranases all belong to the GH49 family 19 . In this study, the cloning and sequencing of a GH49 dextranase from P. pinophilum SMCU3-14 and its heterologous expression in an alternative bacterial host were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fused galactose inducible GAL10-PYK promoter has recently been used for the production of high levels of hantavirus Puumala nucleocapsid (N) protein (316 mg/l) (Antoniukas et al 2006), and the HeV and NiV nucleocapsid proteins from Hendra and Nipah viruses, has been productively expressed (18-20 mg/l) in S. cerevisiae under the control of the GAL7 promoter (Juozapaitis et al 2007). A GAL1 promoter has also been used to drive the expression of a heterologous dextranase gene in S. cerevisiae, in order to develop a novel toxicity bioassay (Li et al 2006). Similarly, galactose-inducible promoters have been used to drive the expression of heterologous enzymes, allowing production of valuable metabolites in S. cerevisiae, like genistein (Katsuyama et al 2007) and the artemisinin precursor amorpha-4,11-diene (Lindahl et al 2006).…”
Section: Controlled Expression Using Endogenous Promotersmentioning
confidence: 99%
“…Dextranolytic enzymes are also being used in the synthesis of potentially valuable oligosaccharides (Goulas et al 2004) and as possible mouthwash ingredients (Kim et al 2002). Furthermore, a cloned Penicillium minioluteum dextranase has recently been used to engineer a mycotoxindetecting yeast-based bioassay (Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%